Interlayer mixing in lithium nickel manganese cobalt oxide cathode materials for rechargeable lithium batteries - Tan, Tze Qing
Composition of LiNi1/3Mn1/3Co1/3O2 and its analogous Li[(Ni0.5Mn0.5)1-xCox]O2 were prepared by conventional solid state method to evaluate the effect of reducing cobalt contents to the layered rock salt-type cathode materials. Structural analysis using Rietveld refinement of conventional XRD data revealed that the amount of cobalt contents is highly correlated to their structural stability. Solid solution limit for phasepure samples that were prepared is about x > 0.2 for Li[(Ni0.5Mn0.5)1-xCox]O2. The amount of interlayer mixing increased for samples contain 20% or less cobalt contents. The results showed that the minimum amount of interlayer mixing that could be achieved is about 3.8% for the composition of LiNi0.4Mn0.4Co0.2O2 that was prepared at 950 oC in oxygen compared to LiNi1/3Mn1/3Co1/3O2 which is about 2%. However, the amount of interlayer mixing varies as a function of temperatures and conditions. Systematic investigation have been done to optimize refinement parameters and to validate structural model based on LiCoO2 as a standard. On the other hand, the initial charge and discharge capacities during battery cycling for LiNi0.4Mn0.4Co0.2O2 is relatively high which recorded ~323 mAh g-1 and ~229 mAh g-1 respectively. But it has high irreversible capacity loss after a few cycles that are probably due to structural instability during charge and discharge.